Fighting norovirus with a pill: new vaccine shows strong immune response - Flitter, Becca (Henry Stewart Talks, 2026)
Infectious diseases, Mucosal vaccines, Norovirus vaccines, Future vaccine design for aging demographics, Immunosenescence, Norovirus G11, Thermostable oral vaccine platform